Dimensões corporais e reprodução de pequenos mamíferos do Maciço do Urucum, MS, Oeste do Brasil - Mallmann, Aline Stoffels (2007)
The research main goal was to obtain data and analyze the morphology and reproduction of small mammals. Since little data is available, it was analyzed the relation between small mammals body structure (dimensions) and the forest strata. The population variation and its reproduction were analyzed with regard to the season, as well as to its reproductive parameters, such as sexual dimorphism, offspring and testicles size. Although currently the animals are in a museum (UFSM), they were previously captured using 72 pitfalls, which were positioned in three areas. This was done for 5 days every month, from December 2000 to September 2002. External measurements, such as body size, arm, leg, tail, ear, whiskers, toe size and biggest toe, were taken for all species with adequate number of adults. The most frequent species found were the rodents Akodon toba, Calomys cf. callosus, Oecomys bicolor and Oryzomys nitidus. The genders were analyzed separately due to the existing differences in sex. The sizes were then compared through the Multivariate Analysis of Covariance (MANCOVA) between species. A Discriminant Analysis was performed to verify which morphological variable better explain the difference between the samples. The characteristic that better explained the differences between the species was the tail, which was relatively short for terrestrial species (such as Akodon toba e Calomys cf. callosus) and comparatively long (similar to the body size) for the species Oecomys bicolor e Oryzomys nitidus. The wider foot and longer whiskers for O. bicolor, the bigger toe for O. nitidus, longer tail and toes for both are characteristics which are probably related to their arboreal and scansorial habitat, respectively. These species were more abundant in the warm season and beginning of the cold season, there have not been major differences between males and females. There was, though, a difference between youngsters and adults for A. toba e O. nitidus. Akodon toba had more youngsters in the warm season, while the O. nitidus had it during the cold season. Available resources influenced the reproduction of males and females, as well as the occurrence of young and adults in the population. Callomys cf. callosus presented larger nesting (5.17) while O. bicolor had smaller ones (2.33). Only Callomys cf. callosus presented sexual dimorphism with regard to the body length and tail, with males bigger in size. That shows a promiscuous mating system for these species. The testicles analysis (internal measurement) with reference to the scrotal testes (external measurement) had no difference for these species, but they were bigger for bigger body size for each species.